2012
DOI: 10.1007/s10008-012-1684-9
|View full text |Cite
|
Sign up to set email alerts
|

NO x conversion on porous LSF15–CGO10 cell stacks with KNO3 or K2O impregnation

Abstract: In the present work it was investigated how addition of KNO 3 or K 2 O affected the NO x conversion on LSF15-CGO10 (La 0.85 Sr 15 FeO 3 -Ce 0.9 Gd 0.1 O 1.95 ) composite electrodes during polarisation. The LSF15-CGO10 electrodes were part of a porous 11-layer cell stack with alternating layers of LSF15-CGO10 electrodes and CGO10 electrolyte. The KNO 3 was added to the electrodes by impregnation, and kept either as KNO 3 in the electrode or thermally decomposed into K 2 O before testing. The cell stacks were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The presence of such a process on perovskite/CGO10 electrodes is in good agreement with previous findings in our group. 28,30 Processes on impregnated electrodes…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such a process on perovskite/CGO10 electrodes is in good agreement with previous findings in our group. 28,30 Processes on impregnated electrodes…”
Section: Discussionmentioning
confidence: 99%
“…Both the impregnation of KNO 3 and MnOx can cause the decrease of the polarization resistance related to the formation of NO 2 from NO oxidation. They [26][27] (LSM-GDC) composite electrodes respectively based on the GDC electrolyte cell stacks. Results showed that high NOx conversion can be obtained with the NOx adsorption layer between 300°C and 500°C.…”
Section: Introductionmentioning
confidence: 99%
“…13−15 Frequently, a composite electrode is applied, i.e., an electrode with both an electron conducting phase (for instance, a perovskite) and an O 2− conducting phase (for instance, yttria stabilized zirconia (YSZ) or CGO). 13,15,16 An obstacle in the investigation and understanding of electrochemical deNO x is a limited knowledge of the adsorption of NO x on the electrode materials, and how this adsorption changes in the temperature ranges investigated for electrochemical deNO x (usually 300− 600 °C) and depending on the presence of NO or NO 2 . The aim in this work is to apply DRIFT (diffuse reflectance infrared Fourier transform) spectroscopy to study the NO x adsorption at conditions relevant for electrochemical deNO x .…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the investigation of suitable electrode materials for electrochemical deNO x a major challenge is to find electrode materials that have a sufficiently high activity and selectivity, i.e., which are capable of reducing NO x but not O 2 , as reduction of O 2 is a competing reaction on the cathode . Several electrode materials have been investigated for electrochemical deNO x , for example, noble metals, spinels, and perovskites. Frequently, a composite electrode is applied, i.e., an electrode with both an electron conducting phase (for instance, a perovskite) and an O 2– conducting phase (for instance, yttria stabilized zirconia (YSZ) or CGO). ,, An obstacle in the investigation and understanding of electrochemical deNO x is a limited knowledge of the adsorption of NO x on the electrode materials, and how this adsorption changes in the temperature ranges investigated for electrochemical deNO x (usually 300–600 °C) and depending on the presence of NO or NO 2 . The aim in this work is to apply DRIFT (diffuse reflectance infrared Fourier transform) spectroscopy to study the NO x adsorption at conditions relevant for electrochemical deNO x .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation